Study of the frequency of allergens in cosmetics components in patients with suspected allergic contact dermatitis Estudo da frequência dos alérgenos da bateria de cosméticos em pacientes com suspeita de dermatite alérgica de contato - Eliane Aparecida Silva; Marcia Regina Miras Bosco; Érika Mozer (Sociedade Brasileira de Dermatologia, 2012)
BACKGROUND: Contact dermatitis to cosmetics is a common dermatosis, especially in adults and professionals who handle them. OBJECTIVE: The objective of this study was to evaluate the frequency of sensitization to cosmetics' components in patients with suspected allergic contact dermatitis and to identify the main sensitizers related to occupational contact dermatitis. METHODS: During the period of January 2008 to June 2010, all the patients with a presumptive diagnosis of allergic contact dermatitis to cosmetics were selected. The patients were submitted to the patch tests of cosmetics series, composed by ten substances. RESULTS: Among the 147 patients studied sensitization to cosmetics components occurred in 31,29% of the cases, 14 of those (19,18%) equally corresponding to BHT and triethanolamine substances, 13 (17,81%) to ammonium thioglycolate, 09 to sorbic acid (12,33%), 08 to tosilamida (10,95%), 06 to germall (8,22%). The other elements tested showed indices of 5% or less. A higher frequency of contact dermatitis to cosmetics was observed in women and the age most affected was concordant with the age range of greatest professional activity of the population. CONCLUSION: Allergic contact dermatitis was more frequently associated with Triethanolamine, BHT and ammonium thioglycolate, and the relation with occupational contact dermatitis was discreet. FUNDAMENTOS: A dermatite de contato por cosméticos é uma dermatose relativamente comum, sobretudo em adultos e em profissionais que os manipulam. OBJETIVO: O objetivo do estudo foi avaliar a freqüência de positividade aos componentes de cosméticos, em pacientes com suspeita de dermatite alérgica; e identificar os principais sensibilizantes relacionados à dermatite de contato ocupacional. MÉTODOS: Durante o período de janeiro de 2008 a junho de 2010 foram selecionados todos os pacientes com hipótese de dermatite alérgica de contato a cosméticos. Os pacientes foram submetidos aos testes epicutâneos com bateria de cosméticos, composta por dez substâncias. RESULTADOS: Dos 147 pacientes estudados, a sensibilização aos componentes do cosmético ocorreu em 31,29% dos casos, sendo 14 (19,18%) corresponderam igualmente às substâncias BHT e trietanolamina, 13 (17,81%) ao tioglicolato de amônia, 09 ao ácido sórbico (12,33%), 08 tonsilamida (10,95%), 06 germal (8,22%). Os demais elementos testados proporcionaram índices iguais ou inferiores a 5%. Observou-se maior freqüência de dermatite de contato aos componentes da bateria de cosméticos em mulheres e a idade mais acometida foi concordante com a faixa etária de maior atividade profissional da população. CONCLUSÕES: Houve maior freqüência de dermatite alérgica de contato pelas substâncias trietanolamina, BHT e tioglicolato de amônia, demonstrando pouca associação à dermatite de contato ocupacional.